1976
DOI: 10.1136/vr.98.6.110
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellosis in apparently healthy dogs

Abstract: When rectal swabs were examined from 672 dogs in Tehran, Iran, 52 (7-7 per cent) yielded Salmonellae of 20 different serotypes. The 672 dogs examined comprised 472 household pets, 181 kennel dogs and 19 strays. Tehy showed an incidence of 4-4 per cent, 15-5 per cent and 15-8 per cent respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…The fact that household dogs generally show lower isolation rates of salmonellae and campylobacters than stray dogs (Shimi et al, 1976;Simpson et al, 1981;Fox, 1990;Workman et al, 2005) was shown by our findings as well. These highly prevalent gastrointestinal pathogens in shelters may increase the risks of (1) nosocomial transmission between dogs, (2) zoonotic transmission to workers in shelters and people adopting dogs from shelters, and (3) environment contamination potential (Sokolow et al, 2005;Wright et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…The fact that household dogs generally show lower isolation rates of salmonellae and campylobacters than stray dogs (Shimi et al, 1976;Simpson et al, 1981;Fox, 1990;Workman et al, 2005) was shown by our findings as well. These highly prevalent gastrointestinal pathogens in shelters may increase the risks of (1) nosocomial transmission between dogs, (2) zoonotic transmission to workers in shelters and people adopting dogs from shelters, and (3) environment contamination potential (Sokolow et al, 2005;Wright et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Serovar Braenderup is not commonly associated with dogs, but it was once isolated in Iran (Shimi et al . ), and recently from a dog in Texas, United States (Reimschuessel et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…; Shimi et al . ). More recent information on the carrier state in dogs is available from the United States (Jay‐Russell et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, prevalence of S almonella spp . in stray or shelter dogs has been shown to be higher than in client‐owned household dogs: 6.3% versus 2.1% (Tsai et al., 2007) and 15.8% versus 4.4% (Shimi et al., 1976).…”
Section: Introductionmentioning
confidence: 99%